Buckling behavior of clamped laminated composite cylindrical shells under external pressure using finite element method - Abdi, Behzad (2012)
In this study, the elastic buckling behavior of clamped laminated composite cylindrical shells under external pressure was studied. The Finite Element Method (FEM) was used to predict the critical elastic buckling pressure behavior when composite cylindrical shells were subjected to external pressure. The edges of the cylindrical shell ends were completely constrained to simulate clamped end conditions. The influences of parameters such as wall thickness, fiber angle, number of layers and L/R ratio of laminated composite cylindrical shells on critical buckling pressure were studied. It has been found that the under external pressure, the thickness and the fiber angle of the layers have the most significant effect on the critical buckling pressure.